2017
DOI: 10.3390/molecules22050680
|View full text |Cite
|
Sign up to set email alerts
|

Innovative “Green” and Novel Strategies for the Extraction of Bioactive Added Value Compounds from Citrus Wastes—A Review

Abstract: Citrus is a major processed crop that results in large quantities of wastes and by-products rich in various bioactive compounds such as pectins, water soluble and insoluble antioxidants and essential oils. While some of those wastes are currently valorised by various technologies (yet most are discarded or used for feed), effective, non-toxic and profitable extraction strategies could further significantly promote the valorisation and provide both increased profits and high quality bioactives. The present revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
134
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(167 citation statements)
references
References 148 publications
(185 reference statements)
6
134
0
15
Order By: Relevance
“…5 However, an efficient extraction process is necessary to obtain added-value products from biowastes. Over the last few years, suitable extraction methods have been investigated to obtain phytochemical compounds from biowastes, with higher efficiencies and reduced extraction times, [6][7][8][9][10] ultrasound-assisted extraction (UAE) being one of the most promising among other novel extraction techniques, since it needs lower amounts of solvents and reduced extraction times compared with conventional methods (solid-liquid or liquid-liquid extraction, grinding, maceration (soaking), percolation, counter-current extraction, pressurized liquid extraction, Soxhlet, etc.). 11,12 First, cavitation is the crucial effect of ultrasound because it leads to cell disruption and enhances mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, an efficient extraction process is necessary to obtain added-value products from biowastes. Over the last few years, suitable extraction methods have been investigated to obtain phytochemical compounds from biowastes, with higher efficiencies and reduced extraction times, [6][7][8][9][10] ultrasound-assisted extraction (UAE) being one of the most promising among other novel extraction techniques, since it needs lower amounts of solvents and reduced extraction times compared with conventional methods (solid-liquid or liquid-liquid extraction, grinding, maceration (soaking), percolation, counter-current extraction, pressurized liquid extraction, Soxhlet, etc.). 11,12 First, cavitation is the crucial effect of ultrasound because it leads to cell disruption and enhances mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…China is followed by Spain, Morocco, Turkey, Brazil, and Egypt, while Spain is the world's largest exporter of fresh mandarins, accounting for over 50% of the world's exports (FAO ). It has recently been reported that mandarins represent 22% of world's citrus production (FAO ) or positioned as second most produced citrus in the world (Putnik and others ), highlighting the importance of this crop. Anatomically speaking, mandarins are divided into pericarp (peel) and endocarp, with the pericarp branching into epicarp (flavedo) and mesocarp (albedo) see Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Many reports show that thermal processing of foods adversely affects the nutritional content and sensory properties of foods, but thermal treatment is still necessary for inactivating microbial pathogens and enzymes, in order to prolong shelf‐life (van Boekel et al., ). Raw fruits and vegetables (Poojary et al., ; Putnik et al., ; Putnik et al., ), their products (Bursać Kovačević et al., ), and byproducts (Putnik et al., ) are among the most sensitive materials for (thermal) processing, yet innovative applications of (nonthermal) technology can decrease or alleviate deterioration of important biologically active compounds. In these examples, use of multivariate statistics, especially multivariate regression, has enabled optimization of parameters.…”
Section: Chemometrics In Food‐related Disciplinesmentioning
confidence: 99%